Social Capital Trends in Germany in the Face of the Covid-19 Pandemic: A Research Note - Burrmann, Ulrike; Mutz, Michael; Sielschott, Stephan; Braun, Sebastian (Frontiers in Political Science, 2022)
This research note assesses social capital trends in Germany during the Covid-19 pandemic. A trend design with large-scale surveys is used to analyze social capital levels in Germany. Trends reported here inform about changes of social capital levels during the ‘second lockdown’ of the Covid-19 pandemic in December 2020 when containment and mitigation policies were in effect throughout the country. Findings of this study allow some conclusions regarding the pandemic’s effects on social capital levels in Germany. Neither did the pandemic lead to a massive overall decline of social capital, nor did it strengthen the social capital level. Members in voluntary organizations have more social capital compared to non-members, a difference that is found before as well as during the pandemic. Vulnerable groups, however, have a harder time generating social capital.